1973
DOI: 10.1111/j.1476-5381.1973.tb08160.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzyme inhibitors of catecholamine metabolism and of haloperidol on the pancreatic secretion induced by l‐DOPA and by dopamine in dogs

Abstract: Summary1. Effects of inhibitors of DOPA decarboxylase, dopamine 8-hydroxylase and monoamine oxidase, and haloperidol on the secretion of pancreatic juice induced by L-DOPA and dopamine were studied in preparations of the isolated blood-perfused canine pancreas. 2. The increased secretion induced by the infusion of L-DOPA (100 ,ug/min) was completely antagonized by Ro 4-4602 (300 ug), a DOPA decarboxylase inhibitor. 3. The secretogogue effect of dopamine (1-10 ug) intra-arterially was not affected by Ro 4-4602,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

1974
1974
1984
1984

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 13 publications
3
27
0
Order By: Relevance
“…* Presented in part at the 13 During investigations on monoaminergic mechanisms in pancreatic islets we employed the dopaminergic antagonist haloperidol, which is purported to be a specific dopamine receptor blocking agent in tissues such as brain [5], exocrine pancreas [6] and renal and mesenteric vessels [7]. Using the isolated, perfused canine pancreas it was noted that this dopaminergic antagonist inhibited release of both glucagon and insulin.…”
mentioning
confidence: 99%
“…* Presented in part at the 13 During investigations on monoaminergic mechanisms in pancreatic islets we employed the dopaminergic antagonist haloperidol, which is purported to be a specific dopamine receptor blocking agent in tissues such as brain [5], exocrine pancreas [6] and renal and mesenteric vessels [7]. Using the isolated, perfused canine pancreas it was noted that this dopaminergic antagonist inhibited release of both glucagon and insulin.…”
mentioning
confidence: 99%
“…The responses to dopamine were modified by haloperidol, a dopamine receptor antagonist (6). We suggested that there were specific receptors for the secretion of the pancreatic juice by dopamine and that dopamine may play a physiological role in the secretory mechanism of the dog pancreas.…”
mentioning
confidence: 89%
“…Details of the preparation have been described elsewhere (4,6). The rate of pancreatic secretion was measured using a drop counter.…”
mentioning
confidence: 99%
“…The pancreas was perfused with the animal's own blood from the femoral artery as described previously (Hashimoto et al, 197 1;Furuta et al, 1973). The rate of the exocrine secretion of the pancreas was measured by a drop counter and the blood flow was monitored by a magnetic flowmeter (Nihon Kohden MF-46).…”
Section: Methodsmentioning
confidence: 99%
“…This observation gained new interest when Alm, Ehinger & Falck (1969) observed a rapid turnover of 3-(3,4-dihydroxyphenyl)-L-alanine (L-DOPA) to 3-hydroxytyramine (dopamine) in the pancreas and Hashimoto, Satoh & Takeuchi (1971) confirmed the potent effect of L-DOPA and dopamine on exocrine pancreatic secretion. Furthermore it was found (Furuta, Hashimoto, Iwatsuki & Takeuchi, 1973) that the effect of L-DOPA was depressed by inhibitors of dopa decarboxylase whereas the effect of dopamine was potentiated by inhibitors of monoamine oxidase and diminished by haloperidol, a dopamine receptor blocking drug. No changes in pancreatic secretion were observed after injections of ephedrine, phenylephrine, methoxamine and tyramine (Takeuchi, Satoh & Hashimoto, 1973).…”
Section: Introductionmentioning
confidence: 99%